The effects of dietary energy density and lysine:calorie ratio on the growth performance of the 20 to 55 lb pig - Smith, J.W.II; Nessmith, W.B.Jr; Bergstrom, J.R.; Hongtrakul, K.; Loughmiller, J.A.; Musser, R.E.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 336 barrows (initially 21.8 lb and 31 ± 2 d of age) was used to evaluate the results of increasing levels of choice white grease and lysine:calorie ratio on pig performance. Increasing levels of both choice white grease and lysine:calorie ratio improved the growth rate and efficiency of pigs fed from 20 to 55 lb.
Keywords: Swine; Energy density; Lysine:calorie ratio; Performance